Kinematic analysis of the skeleton start - Kivi, D.; Smith, S.; Duckham, R.; Holmgren, B. (ISBS - Conference Proceedings Archive (Konstanz), 2004)
The purpose of this study was to describe the kinematics of the skeleton start and to compare one-foot versus two-foot starting techniques. The first two steps of the start of six national team skeleton athletes were videotaped during competition and analyzed. There were similarities between the kinematics of skeleton starts and sprint starts; however, the results showed that despite similar 50 meter start times there were differences between the one-foot and two-foot groups in knee angles off the block, trunk angle, toe height during recovery, support and flight times, and step length. These results suggest that the one-foot and two-foot starts are unique yet both effective techniques.